Extrusion of ceramic emulsions: Plastic behavior - Vitorino, N.
This paper presents the plastic characterization of several extruded ceramic emulsions prepared by emulsification of different ceramic suspensions: i) red clay, ii) kaolin and iii) alumina, which were performed in order to obtain some insights to upscale the ceramic emulsion extrusion process. Stress-deformation curves obtained by compression of the pre-extruded bodies were used to obtain the plasticity characterization of the emulsions with different water contents. Deformation amplitude, yield stress and rupture stress revealed the most sensitive parameters, thus giving valuable information about the plastic behavior of the ceramic emulsions, as well as important guidelines for extrusion upscale. The microstructural features of the sintered bodies were kept constants even after the extrusion process, making this process be feasible for large-scale production of cellular ceramic bodies. (C) 2014 Elsevier B.V. All rights reserved.